Structure and stability of recombinant bovine odorant-binding protein: I. Design and analysis of monomeric mutants - Stepanenko,Olga V.; Roginskii,Denis O.; Stepanenko,Olesya V.; Kuznetsova,Irina M.; Uversky,Vladimir N.; Turoverov,Konstantin K. (PeerJ, 2016)
Bovine odorant-binding protein (bOBP) differs from other lipocalins by lacking the conserved disulfide bond and for being able to form the domain-swapped dimers. To identify structural features responsible for the formation of the bOBP unique dimeric structure and to understand the role of the domain swapping on maintaining the native structure of the protein, structural properties of the recombinant wild type bOBP and its mutant that cannot dimerize via the domain swapping were analyzed. We also looked at the effect of the disulfide bond by designing a monomeric bOBPs with restored disulfide bond which is conserved in other lipocalins. Finally, to understand which features in the microenvironment of the bOBP tryptophan residues play a role in the defining peculiarities of the intrinsic fluorescence of this protein we designed and investigated single-tryptophan mutants of the monomeric bOBP. Our analysis revealed that the insertion of the glycine after the residue 121 of the bOBP prevents domain swapping and generates a stable monomeric protein bOBP-Gly121+. We also show that the restored disulfide bond in the GCC-bOBP mutant leads to the noticeable stabilization of the monomeric structure. Structural and functional analysis revealed that none of the amino acid substitutions introduced to the bOBP affected functional activity of the protein and that the ligand binding leads to the formation of a more compact and stable state of the recombinant bOBP and its mutant monomeric forms. Finally, analysis of the single-tryptophan mutants of the monomeric bOBP gave us a unique possibility to find peculiarities of the microenvironment of tryptophan residues which were not previously described.
Keywords: Odorant-binding protein; Fluorescence; Protein; Domain swapping; Chemical denaturation; Circular dichroism